Female labor supply and divorce: New evidence from Ireland - Olivier Bargain; Libertad González; Claire Keane; Berkay Özcan (Institute for the Study of Labor (IZA), 2010)
If participation in the labor market helps to secure women's outside options in the case of divorce/separation, an increase in the perceived risk of marital dissolution may accelerate the increase in female labor supply. This simple prediction has been tested in the literature using time and/or spatial variation in divorce legislation (e.g., across US states), leading to mixed results. In this paper, we suggest testing this hypothesis by exploiting a more radical policy change, i.e., the legalization of divorce. In Ireland, the right to divorce was introduced in 1996, followed by an acceleration of marriage breakdown rates. We use this fundamental change in the Irish society as a natural experiment. We follow a difference-in-difference approach, using families for whom the dissolution risk is small as a control group. Our results suggest that the legalization of divorce contributed to a significant increase in female labor supply, mostly at the extensive margin. Results are not driven by selection and are robust to several specification checks, including the introduction of household fixed effects and an improved match between control and treatment groups using propensity score reweighting.
Keywords: J12; J22; D10; D13; K36; 330; Divorce law; natural experiment; labor supply; fixed effects; propensity score; Eherecht; Reform; Scheidung; Frauenerwerbstätigkeit; Arbeitsangebot; Irland